Characterization of tapioca starch oxidized by sodium hypochlorite - Tung, Nguyen Thanh; Khoi, Nguyen Van; Huy, Nguyen Quang; Hung, Nguyen Kim; Hoang, Thai (Vietnam Journal of Chemistry, 2014)
The effects of hypochlorite level (NaOCl, 1%, 2% and 4% w/w) on the structures and physicochemical properties of oxidized tapioca starch were investigated. Carboxyl and carbonyl group contents of oxidized starch increased with increasing NaOCl level. Oxidation caused the outer layer of the starch grain surface to erode away and X-ray diffraction patterns of all the starches remained unchanged after oxidation.